2004
DOI: 10.1117/12.578551
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the elemental composition of Ceres and Vesta: Dawn"s gamma ray and neutron detector

Abstract: Dawn is a NASA discovery mission that will explore the main belt asteroids (1) Ceres and (4) Vesta. Ceres and Vesta are among the oldest bodies in the solar system and represent very different evolutionary paths. By studying these ancient, complementary asteroids, we will answer fundamental questions about the early solar system and planetary formation processes.The Dawn payload consists of a Framing Camera (FC), a visual and infrared mapping spectrometer (VIR), and a Gamma Ray and Neutron Detector (GRaND). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The Dawn spacecraft is equipped with a gamma‐ray and neutron detector (GRaND) that will enable measurement and mapping of elemental abundances (potentially O, Si, Fe, Ti, Al, Mg, Ca, K, U, Th, and H) on Vesta’s surface (Prettyman et al. 2003, 2004).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The Dawn spacecraft is equipped with a gamma‐ray and neutron detector (GRaND) that will enable measurement and mapping of elemental abundances (potentially O, Si, Fe, Ti, Al, Mg, Ca, K, U, Th, and H) on Vesta’s surface (Prettyman et al. 2003, 2004).…”
Section: Introductionmentioning
confidence: 91%
“…The Lunar Prospector Gamma Ray Spectrometer (LP‐GRS) can provide information on the analytical performance of GRaND, because LP‐GRS has a γ‐ray sensor (BGO; Bismuth germinate) with approximately the same volume, detection efficiency, and pulse height resolution (Prettyman et al. 2003, 2004).…”
Section: A New Mixing Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceres has an ice-rich crust [Prettyman et al, 2016] that gradually retreats and feeds an exosphere. Based on model calculations of retreating ice, Fanale and Salvail [1989] estimated that the current global water supply rate is 0.03-0.30 kg/s, and Schorghofer [2016b] estimated that 0.2 kg/s of H 2 O is currently output as a direct result of the globally retreating ice; these estimates depend on assumptions about the physical properties of the top tens of meters.…”
Section: Model Of Water Exosphere and Ice Accumulationmentioning
confidence: 99%
“…The performance of GRaND during the Dawn mission was investigated based on results from the Lunar Prospector Gamma Ray Spectrometer (LPGRS), because LPGRS has a gamma ray sensor with approximately the same volume, detection efficiency, and pulse height resolution . On this basis, Prettyman et al (2004) concluded that the spectrum obtained at LAMO is enough above background to map abundances of major rock forming elements, radioactive elements, and light elements such as H, C, and N at Vesta and Ceres. Therefore, GRaND data sets should allow construction of the mixing diagram employing [M/Si] plot between basaltic eucrite, cumulate eucrite, and diogenite, which is consistent with previous geochemical and petrographical studies (e.g., Mittlefehldt 2003;Mittlefehldt et al 1998).…”
Section: A Two-dimensional Diagram For a Mixing Model With Three Endmmentioning
confidence: 99%